Preparation method and application of ZIF-8 loaded bioactive glass organic-inorganic nanofiber membrane
Through the preparation method of ZIF-8 bioactive glass organic-inorganic nanofiber membrane, the problems of complex steps, poor breathability, insufficient sustained release effect and insufficient hydrophilicity in the prior art are solved, and the sustained release of high-efficiency drugs and achieved The effect of wound healing.
Patent Information
- Application Number
- CN202411595078.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing bioactive glass fiber membrane preparation methods have problems such as complex steps, poor breathability, insufficient sustained release effect and insufficient hydrophilicity, which is difficult to meet the needs of wound healing.
Using the preparation method of organic-inorganic nanofiber membrane of ZIF-8 bioactive glass, the electrospinning process combined with the sol-gel method was used to prepare excellent antibacterial properties, controllable hydrophilicity, high breathability and excellent drug relief. nanofiber membrane with release effect.
It achieves high-efficiency drug sustained release, stability and biocompatibility of fiber membranes, promotes wound healing and angiogenesis, and has good tissue repair potential.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical composite materials, and in particular relates to a preparation method and application of an organic-inorganic nanofiber membrane of ZIF-8 bioactive glass. Background Art
[0002] Diabetes not only brings pain to patients, but also affects the speed of wound healing, causing great distress and inconvenience to diabetic patients. Delayed wound closure in diabetic patients is mainly due to the destruction of the cellular microenvironment caused by long-term hyperglycemia, the destruction of ECM structure and function caused by long-term chronic inflammation, and the reduction of growth factor secretion leading to the obstruction of angiogenesis. Finding effective treatment methods for diabetic wounds has always been an important clinical need, so a lot of money and manpower have been invested in the development of advanced and effective skin fiber membranes.
[0003] Bioactive glass (BG) is a class of materials that can repair, replace and regenerate body tissues, and has the ability to form bonds between tissues and materials. It has become a hot research topic in recent years because it can promote the secretion of growth factors, promote the formation of blood vessels, and avoid the occurrence of chronic inflammation as much as possible. Studies have shown that bioactive glass can slowly release Si after being implanted in an organism. 4+ and Ca 2+ As a necessary trace element, Si ions can promote the proliferation and migration of endothelial cells, thereby promoting the expression of growth factors and accelerating the deposition of collagen in wounds. Si ions released by BG can protect endothelial cells under hypoxia and promote the expression of CX43, a gap junction protein in endothelial cells and fibroblasts, thereby promoting angiogenesis. BG can inhibit the inflammatory response at the wound site and accelerate the transformation of macrophage phenotypes, thereby promoting wound healing.
[0004] Metal-organic frameworks (MOFs) are a new type of crystalline material with metal ions as coordination centers. They have extremely high specific surface area, high porosity, structural diversity and unsaturated metal coordination bonds, which are conducive to the modification or grafting of other molecular substances. In recent years, they have been more and more widely used in the biomedical field, especially in the field of drug delivery. ZIF-8 is a type of MOF material with bone induction ability. It has good stability, structural and functional adjustability, and drug loading potential, and has gradually received attention in tissue engineering. On the other hand, ZIF-8 has regular pore size, high specific surface area and unsaturated metal coordination centers, which can better load small molecule drugs and exert a sustained-release effect. Therefore, encapsulating bioactive glass in the ZIF-8 organic framework can not only release Si 4+ , Ca 2+ , and Zn 2+ , which will help accelerate wound healing.
[0005] Nanofiber membranes provide an extracellular skin-like matrix that can better replenish cells and easily bind bioactive molecules, enhancing the penetration of nutrients and oxygen. Therefore, large-scale preparation of ultrafine nanofiber membranes with ultrathin diameter, high permeability, good interconnected pore structure and biocompatibility as biomaterials is of great significance.
[0006] In response to the above problems, Patent 201410466451.4 discloses a bioactive glass fiber-polycaprolactone composite membrane and its preparation method and application. The bioactive glass fiber with nanopores is prepared by combining electrospinning technology with sol-gel method, and then the bioactive glass fiber is dispersed in a solution containing polycaprolactone, spread on a glass dish, and dried to obtain a membrane. The upper large pore is 20 to 100 μm, and the small pore is less than 2 μm. However, this method has the following problems: (1) The bioactive glass prepared is produced by electrospinning technology, which is relatively complicated, with many preparation steps and is time-consuming.
[0007] (2) The prepared bioactive glass-polycaprolactone composite membrane is obtained by spreading the solution and then solidifying it. The pores of this composite membrane will be blocked by polycaprolactone, resulting in poor air permeability.
[0008] (3) The bioactive glass is wrapped inside the polycaprolactone membrane. However, polycaprolactone is a hydrophobic membrane, so it is difficult to release the bioactive glass slowly when it is attached to the bone tissue. Therefore, the sustained release effect of the composite membrane is low.
[0009] In view of the problems existing in the above technologies, we urgently need to seek a method for preparing a fiber membrane with simple process, strong hydrophilicity, excellent sustained-release effect and good air permeability and apply it to wound healing. Summary of the invention
[0010] In order to improve the existing fiber membranes, such as poor air permeability, unclear sustained release effect, and lack of hydrophilicity, the present invention mainly discloses a preparation method and application of an organic-inorganic nanofiber membrane of ZIF-8 bioactive glass. The preparation method is simple to operate, and the preparation conditions are mild and controllable. The prepared organic-inorganic nanofiber membrane has excellent antibacterial properties, controllable hydrophilicity, high air permeability, and excellent drug sustained release effect.
[0011] The preparation method and application of the ZIF-8 bioactive glass-carrying organic-inorganic nanofiber membrane of the present invention include the following specific steps: f. Add tetraethyl silicate to a mixed solution of ethanol, water and ammonia water and stir until it is completely dissolved, then place the mixed solution in a four-necked flask and slowly heat it to a certain temperature. Add calcium nitrate tetrahydrate Ca(NO3)2·4(H2O) to the mixed solution for chemical reaction. After the reaction is completed, centrifuge the obtained product several times to collect the precipitate, and then dry the precipitate to obtain a solid powder. Finally, place the dried powder in a muffle furnace for staged calcination to obtain bioactive glass.
[0012] g. Dissolve zinc acetate dihydrate in deionized water (H2O) and stir until it is completely dissolved to obtain zinc acetate dihydrate solution, which is used as solution A. Dissolve 2-methylimidazole in hexadecyltrimethylammonium bromide (CTAB) solution and stir until it is completely dissolved to obtain 2-methylimidazole solution, which is used as solution B. Rapidly mix and stir solutions A and B at a certain mass ratio, then let the mixed solution stand, collect the lower precipitate after standing, centrifuge and wash it several times, and finally dry it to obtain ZIF-8 nanoparticles.
[0013] h. The bioactive glass obtained in step a and the ZIF-8 nanoparticles obtained in step b are added to an ethanol solution for mixing and stirring, and then the mixed solution is centrifuged to obtain a precipitate, and the precipitate is dried to finally obtain a composite material of ZIF-8 coated bioactive glass (GB@ZIF-8).
[0014] i. Add polyvinyl alcohol (PVA) to deionized water and stir until PVA is completely dissolved to obtain a PVA solution, which is used as solution C; add polycaprolactone (PCL) and GB@ZIF-8 to trifluoroethanol (TFE) solution to obtain a PCL / GB@ZIF-8 spinning solution, which is used as solution D.
[0015] j. Inject the solution c and solution d obtained in step e into two identical syringes respectively, and fix the two syringes on a microfluidic dual pump. Then the needles of the two syringes are connected to the two inlets of the Y-type microfluidic chip through a hose, and the Y-type microfluidic chip is fixed on a spinning machine for microfluidic electrospinning process. Set the two-phase injection speed of the microfluidic pump, the high-voltage power supply voltage, and the distance between the chip needle and the receiver, adjust the spinning parameters, and then perform microfluidic electrospinning to obtain PVA / PCL / GB@ZIF-8 organic-inorganic nanofiber membrane.
[0016] Preferably, the mass concentration of tetraethyl silicate described in step a is 5-8%, and the mass ratio of ethanol: water in the mixed solution composed of ethanol, water and ammonia water in step a is 1.5-4.4; the mass ratio of ammonia water to the mixed solution is 0.016-0.02.
[0017] Preferably, the mass concentration of calcium nitrate tetrahydrate Ca(NO3)2·4(H2O) described in step a is 1-1.2%; the reaction time described in step a is 2-4 h; the number of centrifugation described in step a is 3-5 times; the centrifugation speed described in step a is 8000 rad / min-10000 rad / min; and the centrifugation time described in step a is 10-20 min.
[0018] Preferably, the drying time in step a is 4-6 hours; the drying temperature in step a is 40-60°C.
[0019] Preferably, the calcination heating rate in step a is 3-5°C / min; the calcination temperature is 650-700°C; and the calcination time is 10-12 h.
[0020] Preferably, the mass concentration of the zinc acetate dihydrate solution in step b is 4-8%; the stirring time is 2-4 h. The mass concentration of the 2-methylimidazole solution is 12-15%; the stirring time is 2-4 h; and the mass ratio of the A and B solutions is 0.5-1.
[0021] Preferably, the standing time in step b is 6-8 h; the number of centrifugation is 3-5 times, the centrifugal speed is 8000-10000 rad / min, the centrifugal time is 10-20 min; the drying time is 4-6 h; and the drying temperature is 40-60 °C.
[0022] Preferably, the particle diameter of the ZIF-8 nanoparticles described in step b is 125-148 nm.
[0023] Preferably, the mass concentration of the bioactive glass in step c is 0.1-0.2%; the mass concentration of the ZIF-8 nanoparticles is 1-1.2%, wherein the mass ratio of ZIF-8 nanoparticles to bioactive glass is 6-10.
[0024] Preferably, the mixing time in step c is 2-4 h; the number of centrifugal washing is 3-5 times, the centrifugal speed is 8000-10000 rad / min, the centrifugal time is 10-20 min; the drying time is 4-6 h; and the drying temperature is 40-60 °C.
[0025] Preferably, the mass concentration of PVA in step d is 13-15 wt %; the stirring time is 6-8 h, and the stirring temperature is 90-98 ° C.
[0026] Preferably, the mass concentration of the PCL / ZIF-8@GB spinning solution in step d is 15-17 wt %; the stirring time is 4-6 h, and the stirring temperature is 35-40 ° C.
[0027] Preferably, the volume of the two identical syringes in step e is 5-550 mL. The inner channel diameter of the Y-shaped microfluidic chip is 4-6 mm.
[0028] Preferably, the two-phase injection speed of the microfluidic pump described in step e is C solution (0.2-0.5 mL / h), D solution (0.3-0.5 mL / h), high voltage power supply voltage (12KV-15KV), and the distance between the chip needle and the receiver (25-32 cm).
[0029] Preferably, the fiber diameter of the PVA / PCL / ZIF-8@GB composite nanofibers described in step e is 440-560 nm.
[0030] Preferably, the tensile strength of the PVA / PCL / ZIF-8@GB composite nanofiber membrane described in step e is in the range of 20.5-24.6 MPa.
[0031] Preferably, the weight average molecular weight of the polycaprolactone PCL of the present invention is 80,000; Droplet microfluidics precisely controls the flow of multiple fluids at the micro-nano scale, and produces discrete droplets from mutually incompatible multiphase fluids in microchannels to prepare MOF-coated bioglass microspheres. This technology can generate micro-nano droplets with adjustable structure and controllable composition in a high-throughput manner, with the advantages of good monodispersity, no cross-contamination, high controllability and high reproducibility. The prepared MOF@BG microspheres were electrospun with inorganic polymers PCL and PVA by microfluidics to obtain Zn 2+ , Ca 2+ and Si 4+ Composite micro-nano skin membrane. After implantation into the organism, the MOF-coated bioglass microspheres dissolved Zn 2+ , Ca 2+ and Si 4+ After ion exchange, Si-O-Si bonds are broken, forming Si-OH and polymerizing with each other to form a silica-rich gel layer, which increases the pH value around the material. 2+ and (PO4) in body fluids 3- Reaction, forming calcium-phosphorus enrichment on the surface of the material, and finally transitioning to a hydroxyapatite layer, which is evenly deposited on the surface of the skin membrane. Studies have shown that Si 4+It is an essential trace element for the human body, which can promote the proliferation and migration of endothelial cells and accelerate the deposition of collagen at the wound site. Bioglass can inhibit the inflammatory response at the wound site and accelerate the phenotypic conversion of macrophages, thereby promoting wound healing. The micro-nano skin fiber membrane loaded with BG@ZIF-8 microspheres has great potential in tissue repair by accelerating wound healing and having good mechanical properties.
[0032] The beneficial effects of the present invention are as follows: 1. The ZIF-8 encapsulated bioactive glass prepared by the present invention contains Ca 2+ , Si 4+ , Zn 2+ Three ions that are beneficial to tissue regeneration.
[0033] 2. The PVA / PCL / ZIF-8@GB organic-inorganic nanofiber membrane prepared by the present invention has high efficient drug sustained release, high stability, high air permeability and high mechanical strength.
[0034] 3. The hydrophilicity of the PVA / PCL / ZIF-8@GB organic-inorganic nanofiber membrane prepared by the present invention can be regulated by the ratio of PVA and PCL.
[0035] 4. The preparation method of the PVA / PCL / ZIF-8@GB organic-inorganic nanofiber membrane prepared by the present invention has simple equipment, convenient operation, and can achieve large-scale preparation.
[0036] 5. The PVA / PCL / ZIF-8@GB organic-inorganic nanofiber membrane prepared by the present invention has excellent biocompatibility and tissue compatibility.
[0037] 6. The PVA / PCL / ZIF-8@GB organic-inorganic nanofiber membrane prepared by the present invention has a rich porous structure and a high surface area, which can promote the recruitment of cells.
[0038] 7. The PVA / PCL / ZIF-8@GB organic-inorganic nanofiber membrane prepared by the present invention can promote angiogenesis, collagen deposition and the formation of granulation tissue, and effectively prevent infection of full-thickness skin defect wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the SEM image of the BG@ZIF-8 nanomaterial prepared in Example 1; Figure 2 This is the EDS scanning element analysis diagram of the BG@ZIF-8 nanomaterial prepared in Example 1; Figure 3 This is a SEM image of the PCLPVA / BG@ZIF-8 organic-inorganic nanofiber composite membrane prepared in Example 2; Figure 4 This is a diagram of the mechanical tensile properties of the PCLPVA / BG@ZIF-8 organic-inorganic nanofiber composite membrane prepared in Example 2.
[0040] Figure 5 Ion release performance diagram of PCLPVA / BG@ZIF-8 organic-inorganic nanofiber composite membrane prepared in Example 3 Figure 6 Antibacterial performance of PCLPVA / BG@ZIF-8 organic-inorganic nanofiber composite membrane prepared in Example 3 Figure 7 This is a diagram of the experimental process of using the PCLPVA / BG@ZIF-8 organic-inorganic nanofiber composite membrane prepared in Example 3 for wound healing treatment. Specific implementation examples
[0041] The following is a clear and complete description of the technical solutions in the examples of the present invention. Obviously, the examples described are only part of the examples of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The following experimental methods and detection methods are conventional methods unless otherwise specified; the following reagents and raw materials are commercially available unless otherwise specified.
[0043] Tetraethyl silicate was added to a mixed solution consisting of ethanol, water and ammonia water and stirred until it was completely dissolved to obtain a 5 wt% tetraethyl silicate mixed solution, which was placed in a four-necked flask; the mass ratio of ethanol to water was 1.5, and the mass ratio of ammonia water to the mixed solution was 0.016. Then calcium nitrate tetrahydrate Ca(NO3)2·4(H2O) was added to the mixed solution for chemical reaction for 2h, wherein Ca(NO3)2·4(H2O) accounted for 1wt% of the total solution mass. The obtained product was centrifuged three times to collect the precipitate, the centrifugal speed was designed to be 8000 rad / min, and the centrifugal time was 20 min. Then the precipitate was dried at 40℃ for 4h to obtain a solid powder. Finally, the dried powder was placed in a muffle furnace for staged calcination (heating rate 3℃ / min; calcination temperature 650℃, calcination time 10h) to obtain a bioactive glass with a particle size of 80nm.
[0044] Zinc acetate dihydrate was dissolved in deionized water (H2O) and stirred for 2h until it was completely dissolved to obtain a 4wt% zinc acetate dihydrate solution, which was used as solution A. 2-Methylimidazole was dissolved in hexadecyltrimethylammonium bromide (CTAB) solution and stirred for 2h until it was completely dissolved to obtain a 12wt% 2-methylimidazole solution, which was used as solution B. Solutions A and B were quickly mixed and stirred at a mass ratio of 0.5, and then the mixed solution was allowed to stand for 6h. After standing, the lower precipitate was collected and centrifuged for 3 times (centrifugal speed: 8000 rad / min; centrifugal time 20min), and finally dried at 40℃ for 4h to obtain ZIF-8 nanoparticles with a particle size of 125 nm. Bioactive glass and ZIF-8 nanoparticles were added to an ethanol solution and mixed and stirred for 2h, wherein the mass concentration of ZIF-8 nanoparticles was 1 wt%; the mass ratio of ZIF8 to bioactive glass was 6. Then the mixed solution was centrifuged and washed three times to obtain a precipitate (centrifugal speed of 8000 rad / min, centrifugal time of 20 min), and the precipitate was dried at 40℃ for 6h to finally obtain a composite material of ZIF-8 coated with bioactive glass (GB@ZIF-8). Polyvinyl alcohol (PVA) was added to deionized water and stirred at 90℃ for 6h until PVA was completely dissolved to obtain a 13wt% PVA solution, which was used as solution C; polycaprolactone (PCL) and GB@ZIF-8 were added to trifluoroethanol (TFE) solution and stirred for 4h to obtain a 15wt% PCL / GB@ZIF-8 spinning solution, which was used as solution D.
[0045] Solution C and solution D were injected into two 5 mL syringes respectively, and the two syringes were fixed on the microfluidic dual pump. Then the needles of the two syringes were connected to the two inlets of the Y-type microfluidic chip with a straight channel of 4 mm through a hose, and the Y-type microfluidic chip was fixed on the spinning machine for microfluidic electrospinning process. The two-phase injection speed of the microfluidic pump (C solution: 0.2 mL / h; D solution: 0.3 mL / h), high-voltage power supply voltage (12 KV), and the distance between the chip needle and the receiver (25 cm) were set. After adjusting the spinning parameters, microfluidic electrospinning was performed to obtain a fiber with a diameter of 440 nm and an area of 16 cm. 2 , high strength (20.5MPa) PVA / PCL / GB@ZIF-8 organic-inorganic nanofiber membrane.
[0046] Tetraethyl silicate was added to a mixed solution consisting of ethanol, water and ammonia water and stirred until it was completely dissolved to obtain a 7 wt% tetraethyl silicate mixed solution, which was placed in a four-necked flask; the mass ratio of ethanol to water was 2, and the mass ratio of ammonia water to the mixed solution was 0.018. Then calcium nitrate tetrahydrate Ca(NO3)2·4(H2O) was added to the mixed solution for chemical reaction for 3 h, wherein Ca(NO3)2·4(H2O) accounted for 1.1 wt% of the total solution mass. The obtained product was centrifuged 4 times to collect the precipitate, the centrifugal speed was designed to be 9000 rad / min, and the centrifugal time was 15 min. Then the precipitate was dried at 50 ℃ for 5 h to obtain a solid powder. Finally, the dried powder was placed in a muffle furnace for staged calcination (heating rate 4 ℃ / min; calcination temperature 670 ℃, calcination time 11h) to obtain bioactive glass with a particle size of 105 nm.
[0047] Zinc acetate dihydrate was dissolved in deionized water (H2O) and stirred for 3 h until it was completely dissolved to obtain a 6 wt% zinc acetate dihydrate solution, which was used as solution A. 2-Methylimidazole was dissolved in hexadecyltrimethylammonium bromide (CTAB) solution and stirred for 3 h until it was completely dissolved to obtain a 13 wt% 2-methylimidazole solution, which was used as solution B. Solutions A and B were quickly mixed and stirred at a mass ratio of 0.7, and then the mixed solution was allowed to stand for 7 h. After standing, the lower precipitate was collected and centrifuged for 4 times (centrifugal speed: 9000 rad / min; centrifugal time 15 min), and finally dried at 50 ℃ for 5 h to obtain ZIF-8 nanoparticles with a particle size of 132 nm. Bioactive glass and ZIF-8 nanoparticles were added to an ethanol solution and mixed and stirred for 3 h, wherein the mass concentration of ZIF-8 nanoparticles was 1.1wt%; the mass ratio of ZIF8 to bioactive glass was 8. Then the mixed solution was centrifuged and washed 4 times to obtain a precipitate (centrifugal speed of 9000 rad / min, centrifugal time of 15 min), and the precipitate was dried at 50 °C for 5 h to finally obtain a composite material of ZIF-8 coated with bioactive glass (GB@ZIF-8). Polyvinyl alcohol (PVA) was added to deionized water and stirred at 94 °C for 7 h until PVA was completely dissolved to obtain a 14wt% PVA solution, which was used as solution C; polycaprolactone (PCL) and GB@ZIF-8 were added to trifluoroethanol (TFE) solution and stirred for 5 h to obtain a 16wt% PCL / GB@ZIF-8 spinning solution, which was used as solution D.
[0048] Solution C and solution D were injected into two 20 mL syringes respectively, and the two syringes were fixed on the microfluidic dual pump. Then the needles of the two syringes were connected to the two inlets of the Y-type microfluidic chip with a straight channel of 5 mm through a hose, and the Y-type microfluidic chip was fixed on the spinning machine for microfluidic electrospinning process. The two-phase injection speed of the microfluidic pump (C solution: 0.4 mL / h; D solution: 0.4 mL / h), the high-voltage power supply voltage (12 KV), and the distance between the chip needle and the receiver (28 cm) were set. After adjusting the spinning parameters, microfluidic electrospinning was performed to obtain a fiber with a diameter of 480 nm and an area of 36 cm. 2 , high strength (22.3MPa) PVA / PCL / GB@ZIF-8 organic-inorganic nanofiber membrane.
[0049] Tetraethyl silicate was added to a mixed solution consisting of ethanol, water and ammonia water and stirred until it was completely dissolved to obtain an 8 wt% tetraethyl silicate mixed solution, which was placed in a four-necked flask; the mass ratio of ethanol to water was 4.4, and the mass ratio of ammonia water to the mixed solution was 0.02. Then calcium nitrate tetrahydrate Ca(NO3)2·4(H2O) was added to the mixed solution for a chemical reaction for 4 h, wherein Ca(NO3)2·4(H2O) accounted for 1.2 wt% of the total solution mass. The obtained product was centrifuged 5 times to collect the precipitate, the centrifugal speed was designed to be 10000 rad / min, and the centrifugal time was 20 min. Then the precipitate was dried at 60℃ for 6 h to obtain a solid powder. Finally, the dried powder was placed in a muffle furnace for staged calcination (heating rate 5 ℃ / min; calcination temperature 700 ℃, calcination time 12h) to obtain a bioactive glass with a particle size of 120 nm.
[0050] Zinc acetate dihydrate was dissolved in deionized water (H2O) and stirred for 4 h until it was completely dissolved to obtain an 8 wt% zinc acetate dihydrate solution, which was used as solution A. 2-Methylimidazole was dissolved in hexadecyltrimethylammonium bromide (CTAB) solution and stirred for 4 h until it was completely dissolved to obtain a 15 wt% 2-methylimidazole solution, which was used as solution B. Solutions A and B were quickly mixed and stirred at a mass ratio of 1, and then the mixed solution was allowed to stand for 8 h. After standing, the lower precipitate was collected and centrifuged for 5 times (centrifugal speed: 10000 rad / min; centrifugal time 20 min), and finally dried at 60 ℃ for 6 h to obtain ZIF-8 nanoparticles with a particle size of 148 nm. Bioactive glass and ZIF-8 nanoparticles were added to an ethanol solution and mixed and stirred for 4 h, wherein the mass concentration of ZIF-8 nanoparticles was 1.2wt%; the mass ratio of ZIF8 to bioactive glass was 10. Then the mixed solution was centrifuged and washed 5 times to obtain a precipitate (centrifugal speed of 10000 rad / min, centrifugal time of 20 min), and the precipitate was dried at 60 °C for 6 h to finally obtain a composite material of ZIF-8 coated with bioactive glass (GB@ZIF-8). Polyvinyl alcohol (PVA) was added to deionized water and stirred at 98 °C for 8 h until PVA was completely dissolved to obtain a 15 wt% PVA solution, which was used as solution C; polycaprolactone (PCL) and GB@ZIF-8 were added to trifluoroethanol (TFE) solution and stirred for 6 h to obtain a 17 wt% PCL / GB@ZIF-8 spinning solution, which was used as solution D.
[0051] Solution C and solution D were injected into two 50 mL syringes respectively, and the two syringes were fixed on the microfluidic dual pump. Then the needles of the two syringes were connected to the two inlets of the Y-type microfluidic chip with a straight channel of 6 mm through a hose, and the Y-type microfluidic chip was fixed on the spinning machine for microfluidic electrospinning process. The two-phase injection speed of the microfluidic pump (C solution: 0.5mL / h; D solution: 0.5 mL / h), the high-voltage power supply voltage (15 KV), and the distance between the chip needle and the receiver (32 cm) were set. After adjusting the spinning parameters, microfluidic electrospinning was performed to obtain a fiber with a diameter of 560 nm and an area of 100 cm 2 , high strength (24.6MPa) PVA / PCL / GB@ZIF-8 organic-inorganic nanofiber membrane.
[0052] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing an organic-inorganic nanofiber membrane of ZIF-8 bioactive glass and its application, characterized in that: The following steps are involved: a. Add tetraethyl silicate to a mixed solution of ethanol, water and ammonia water and stir until it is completely dissolved, then place the mixed solution in a four-necked flask and slowly heat it to a certain temperature. Add calcium nitrate tetrahydrate Ca(NO3)2·4(H2O) to the mixed solution for a chemical reaction. After the reaction is completed, centrifuge the obtained product several times to collect the precipitate, and then dry the precipitate to obtain a solid powder. Finally, place the dried powder in a muffle furnace for staged calcination to obtain bioactive glass; b. Dissolve zinc acetate dihydrate in deionized water (H2O) and stir until it is completely dissolved to obtain zinc acetate dihydrate solution, which is used as solution A. Dissolve 2-methylimidazole in hexadecyltrimethylammonium bromide (CTAB) solution and stir until it is completely dissolved to obtain 2-methylimidazole solution, which is used as solution B. Rapidly mix and stir solutions A and B at a certain mass ratio, then let the mixed solution stand, collect the lower precipitate after standing, centrifuge and wash it several times, and finally dry it to obtain ZIF-8 nanoparticles; c. adding the bioactive glass obtained in step a and the ZIF-8 nanoparticles obtained in step b to an ethanol solution for mixing and stirring, then centrifuging and washing the mixed solution to obtain a precipitate, and drying the precipitate to finally obtain a ZIF-8-coated bioactive glass composite material (GB@ZIF-8); d. Add polyvinyl alcohol (PVA) to deionized water and stir until PVA is completely dissolved to obtain a PVA solution, which is used as solution C; add polycaprolactone (PCL) and GB@ZIF-8 to trifluoroethanol (TFE) solution to obtain a PCL / GB@ZIF-8 spinning solution, which is used as solution D; e. Inject the C solution and the D solution obtained in step e into two identical syringes respectively, and fix the two syringes on a microfluidic double pump. Then the needles of the two syringes are connected to the two inlets of the Y-type microfluidic chip through a hose, and the Y-type microfluidic chip is fixed on a spinning machine for microfluidic electrospinning process. Set the two-phase injection speed of the microfluidic pump, the high-voltage power supply voltage, and the distance between the chip needle and the receiver, adjust the spinning parameters, and then perform microfluidic electrospinning to obtain PVA / PCL / GB@ZIF-8 composite nanofibers.
2. The preparation method according to claim 1, characterized in that The mass concentration of tetraethyl silicate described in step a is 5-8%, the mass ratio of ethanol to water in the mixed solution composed of ethanol, water and ammonia water described in step a is 1.5-4.4; the mass ratio of ammonia water to the mixed solution is 0.016-0.
02. The mass concentration of calcium nitrate tetrahydrate Ca(NO3)2·4(H2O) described in step a is 1-1.2%; the reaction time described in step a is 2-4 h; the number of centrifugation described in step a is 3-5 times; the centrifugal speed described in step a is 8000 rad / min-10000 rad / min; the centrifugal time described in step a is 10-20min. The drying time is 4-6h; the drying temperature is 40-60 ℃.
3. The preparation method according to claim 1, characterized in that The calcination heating rate in step a is 3-5°C / min; the calcination temperature is 650-700°C; the calcination time is 10-12 h; the bioactive glass in step a is 80-120 nm.
4. The preparation method according to claim 1, characterized in that The mass concentration of the zinc acetate dihydrate solution in step b is 4-8%; the stirring time is 2-4 h. The mass concentration of the 2-methylimidazole solution is 12-15%; the stirring time is 2-4 h; the mass ratio of the A and B solutions is 0.5-1. The standing time is 6-8 h; the number of centrifugation is 3-5 times, the centrifugal speed is 8000-10000 rad / min, and the centrifugal time is 10-20 min; the drying time is 4-6 h; the drying temperature is 40-60 ° C. The particle diameter of the ZIF-8 nanoparticles is 125-148 nm.
5. The preparation method according to claim 1, characterized in that The mass concentration of the ZIF-8 nanoparticles in step c is 1-1.2%, wherein the mass ratio of the ZIF-8 nanoparticles to the bioactive glass is 6-10. The mixing time is 2-4 h; the number of centrifugal washing is 3-5 times, the centrifugal speed is 8000-10000 rad / min, the centrifugal time is 10-20 min; the drying time is 4-6 h; and the drying temperature is 40-60 °C.
6. The preparation method according to claim 1, characterized in that The mass concentration of PVA in step d is 13-15wt%; the stirring time is 6-8 h, and the stirring temperature is 90-98 °C; the mass concentration of the PCL / ZIF-8@GB spinning solution is 15-17 wt%; and the stirring time is 4-6 h.
7. The preparation method according to claim 1, characterized in that The volume of the two identical syringes in step e is 5-50 mL. The inner channel diameter of the Y-shaped microfluidic chip is 4-6 mm; the two-phase injection speed of the microfluidic pump is C solution (0.2-0.5 mL / h), D solution (0.3-0.5 mL / h), high voltage power supply voltage (12KV-15KV), and the distance between the chip needle and the receiver (25-32 cm).
8. The preparation method according to claim 1, characterized in that The fiber diameter of the PVA / PCL / ZIF-8@GB composite nanofibers described in step e is 440-560 nm.
9. The preparation method according to claim 1, characterized in that The tensile strength of the PVA / PCL / ZIF-8@GB composite nanofiber membrane described in step e is in the range of 20.5-24.6 MPa.
Citation Information
Patent Citations
Bioactive glass fiber-polycaprolactone composite membrane, its preparation method and application
CN104225660B
Cited By
Carbon quantum dot gel material based on front-end polymerization means and preparation method and application of composite film of carbon quantum dot gel material
CN120888027A
A preparation method and application of a carbon quantum dot gel material based on a front-end aggregation means and a composite film thereof
CN120888027B